Deadline [compact disc, unabridged] - Sandford, John, 1944 February 23- (Sandford, John, 1944 February 23- Virgil Flowers novels, 2014)
In Southeast Minnesota, a school board meeting is coming to an end. The board chairman announces that the rest of the meeting will be closed, due to personnel issues. The proposal up for a vote before them is whether to authorize the killing of a local reporter. The vote is favorable. Meanwhile, Virgil Flowers is helping out a friend, when he gets a call from Lucas Davenport. A murdered body has been found, and the victim is a local reporter.